2022
DOI: 10.2214/ajr.21.26376
|View full text |Cite
|
Sign up to set email alerts
|

Progression Rates of LR-2 and LR-3 Observations on MRI to Higher LI-RADS Categories in Patients at High Risk of Hepatocellular Carcinoma: A Retrospective Study

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[ 20 ] Two of the patient‐level studies relied on imaging reports, with Ranathunga et al being the only study to independently review imaging studies. [ 21 ] The study by Ranathunga and colleagues was also the only study to perform patient‐level analysis using LI‐RADS Version 2018 and reported 11.1% of 36 patients developed HCC during the mean follow‐up 17.8‐month study period. [ 21 ] Across all three studies, the proportion of patients who developed HCC ranged from 11.1% to 24.5%, and an additional 8%–22.2% developed an LR‐4 observation during the median follow‐up of 9–17.9 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Two of the patient‐level studies relied on imaging reports, with Ranathunga et al being the only study to independently review imaging studies. [ 21 ] The study by Ranathunga and colleagues was also the only study to perform patient‐level analysis using LI‐RADS Version 2018 and reported 11.1% of 36 patients developed HCC during the mean follow‐up 17.8‐month study period. [ 21 ] Across all three studies, the proportion of patients who developed HCC ranged from 11.1% to 24.5%, and an additional 8%–22.2% developed an LR‐4 observation during the median follow‐up of 9–17.9 months.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 13 eligible studies, including 11 full texts and two abstracts. [15][16][17][18][19][20][21][22][23][24][25][26][27] Four studies exclusively evaluated LR-3 observations, one evaluated LR-4 observations, and the remaining eight evaluated both LR-3 and LR-4 observations (Figure 1). Characteristics of studies are detailed in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In clinical practice, an increasing number of subcentimeter size hypervascular observations are observed on contrast-enhanced computed tomography (CECT) and magnetic resonance (MR) imaging (MRI) studies, with the cumulative risk of HCC progression in these observations being higher than in hypovascular nodules. 7,8 Ranathunga et al 9 showed that the rate of progression from LR-3 to LR-4 was 22.22% (►Fig. 2A-F) and from LR-3 to LR-5 was 11.1% at least 12 months after the initial observation was detected.…”
Section: Lr-3mentioning
confidence: 99%
“…According to LI-RADS v2018, repeat or alternative diagnostic imaging within 3-6 months is recommended for LR-3 observations [6,9]. However, previous longitudinal studies have shown a wide variation in the progression rate from LR-3 to higher categories, ranging from 6-55.6% [10][11][12][13][14][15][16][17][18][19][20]. This variability poses challenges for standardized monitoring strategies for both radiologists and referring clinicians, as it creates uncertainty regarding the rate of malignancy associated with LR-3 observations and their progression.…”
Section: Introductionmentioning
confidence: 99%